Building on Strengths: Maya Midwifery International. Issue 2 (March 2017) - Callister, Lynn Clark
Abstract : Maya Midwifery International provides care to mothers and babies in areas with low resources in Guatemala. Our global health nursing expert, Dr. Callister, discusses how this initiative is an example of working within the limits of available resources, addressing social determinants of health, and collaborating to enhance ability for indigenous providers to play a vital role in healthcare delivery that is safe, culturally appropriate, and cost effective.